The Ergonomic Analysis of the Airline Passengers Message Service to Improve the Flight Safety - Poerwanto, Eko; Sajati, Haruno; Andaruwati, Ragil (SENATIK STT Adisutjipto, 2018)
A message/complaint service is a very strategic facility for all stakeholders of an industrial organization. The ergonomic message/ complaint service in the aviation industry is an ergonomics approach based on a standard service system provided by an airline which iseasily accessed/ used and the given response is according to the airline passenger expectations. This research was started by observing the message service/ complaint facilities in the aviation industry (airline) and then the function was analyzed and the improvement to service system facilities was proposed so that it was convenient for the users. The results of the study concluded that there were already message / complaint service facilities in the aviation industry (Airline) but they are not ergonomic and optimal to improve the flight safety, so it is necessary to integrate the message / complaint service system with the safety services to empower the State Safety Program (SSP) according to recommendations of ICAO annex 13, Aircraft accidents and Incident investigations, to improve the flight safety performance.